Job satisfaction and organizational trust as antecedents of organizational commitment in Finnish and Estonian SMEs - Kemell, Kirsi (2015)
This empirical study examines three well-known leadership themes – organizational commitment, job satisfaction and organizational trust – from the perspective of Finnish and Estonian small and medium –sized enterprises (SMEs). The object of the study is to increase knowledge about organizational commitment and job attitudes affecting the formation of commitment. The study is cross-sectional, using previously gathered SME survey data. Organizational commitment is understood as a multidimensional construct. The study is interested especially in its affective component, which is considered to be the deepest form of organizational commitment and usually related to desirable behavioral outcomes. According to the employees’ experiences the three themes correlate positively. When SME organizations engage in development projects trying to enhance their employees’ affective commitment especially job satisfaction and the possibilities for growth (feeling of worthwhile accomplishment from doing the job, challenge and independent thought and action exercised in the job) are important issues to attend to. Just as important is to build and enforce affect-based organizational trust (sharing relationships and emotional investments in working relationships). Managerial implications are very sensible and practical, such as maintaining an open and supportive athmosphere, involving employees in decision making and encouraging the employees to communicate their expectations towards their jobs.